Viral Justice: Law Enforcement in the Social Media Era - Wuysang, Julia Magdalena; Rohani, Siti; Patriani, Ira; Zawawi, Azlyn Ahmad (Nurani, 2024)
The phenomenon of viral justice has significantly transformed the law enforcement process in the era of social media and warrants thorough explanation and evaluation. However, previous research has failed to provide a comprehensive discussion of this phenomenon. This study adopts a descriptive qualitative approach to elucidate and analyze how the characteristics, factors, and implications of viral justice affect the law enforcement process in the social media era, while also addressing the deficiencies in prior studies. The findings of this study unveil three significant conditions for the viral justice phenomenon that have emerged and evolved during the social media era. Firstly, the features of legal violation cases that go viral on social media are complex, encompassing a wide spectrum from minor to major infractions. Secondly, the spread of law enforcement cases on social media is influenced by contextual factors, such as ineffective law enforcement, unaddressed reports, and a perceived lack of transparency in law enforcement. Thirdly, the viral justice phenomenon has significantly impacted the image of law enforcement in the social media era, leading to increasingly complex and contextual perceptions. This is evident in the growing public distrust, delegitimization, and negative associations with the concept of justice. This study also underscores the necessity of investigating the public's motivations for sharing their interactions with law enforcement on social media.